Engineering pedagogical content knowledge: examining correlations with formal and informal preparation experiences - Tyler S. Love; Andrew J. Hughes (SpringerOpen, 2022)
Abstract Background Developing pre-service educators' content and pedagogical knowledge is critical for providing high-quality instruction in science, technology, engineering, and mathematics (STEM) disciplines. Specifically, pedagogical content knowledge (PCK) has been identified as one of the most critically needed research areas within engineering education. However, limited research exists on PCK in engineering education contexts. Therefore, this study investigated whether specific teacher preparation coursework and informal educational experiences influenced high school instructors' teaching of engineering content and practices. Results Using methods similar to a previous study examining technology and engineering educators' teaching of science content and practices (Love & Wells in International Journal of Technology and Design Education 28:395-416, 2018), this study utilized a random sample of 55 Foundations of Technology and Engineering (FoTE) educators from 12 county school systems in the United States. The participants completed the TEES-PCK survey (Love in The Journal of Technology Studies 41: 58-71, 2015), which collected data about their formal and informal preparation experiences. Based on participant responses, eight educators were purposefully selected to be observed while teaching the same FoTE lesson. The observed teaching of engineering content and practices for these eight educators were assigned a rating using the reliable and validated RTOP instrument modified by Love et al. (Journal of Technology Education 29: 45-66, 2017). The TEES-PCK survey data and teaching observation ratings for the eight educators were analyzed using an exploratory correlational design. Spearman's rho tests were used to examine the strength of the relationship between specific formal or informal preparation experiences and their teaching of engineering content and practices. The data were validated through corroboration with FoTE curriculum content analyses, classroom audio recordings and notes, and interviews. The analyses found several formal and informal preparation experiences significantly correlated with participants' teaching of engineering content and practices. Conclusions This study presents recommendations for informing the preparation of educators to teach engineering content and practices in greater depth. The findings provide implications for educational researchers, teacher preparation programs, and in-service professional development efforts. This study contributes to the limited yet essential research area of engineering PCK.